Analysis of a local innovation system: agents and network of relations (2014)
Innovation is a key competitive input for firms and countries and there are well-established models for analyzing the innovation process at the national and regional level. Although we have an abundant literature on industrial districts and innovative agglomerations, there are few case studies that go beyond the description and empirically check the existence of a local innovation system. Hence, in this paper we will discuss a successful experience in innovation, The Knowledge Mile of Gijón, placed at the North of Spain, in order to determine whether the different agents are articulated and interact as a real local innovation system. Using the network analysis technique, we will provide confirmatory evidence showing that (i) relations among agents are dense, cohesive and well-connected and (ii) innovationsupport organizations play an important role in the system.